PENGARUH MANAJEMEN BANK INDUK, KUALITAS ASET, DAN EFISIENSI TERHADAP STABILITAS BANK SYARIAH DI INDONESIA (PERIODE TAHUN 2013-2017) - Lucky Nugroho; Nurul Anisa (Inovbiz: Jurnal Inovasi Bisnis, 2018)
This study aims to determine the effect of parent bank management, asset quality, and efficiency on the stability of Islamic banks. The method used in this study is a quantitative method using multiple linear regression analysis and using spss 23. Statistical software The population in this study are Islamic commercial banks (BUS) that are registered with Bank Indonesia (BI) and the Financial Services Authority (OJK) from 2013 to 2017. Furthermore, Islamic commercial banks continuously and regularly present annual financial reports for the period 2013-2017 and are sampled in this study. The number of samples in this study was 9 Islamic banks with five years of observation as many as 45 samples. Based on the results of the study showed that the management of the parent bank proxied by the directors and commissioners had a significant effect on the stability of Islamic banks due to the many sharia bank directors and commissioners who came from the parent bank which conventional banks had more experience in managing banks. Whereas for asset quality and efficiency variables that are proxied by NPF ratio and BOPO ratio there is no significant effect.